Social Design and pallets reuse: strategies for furniture design/adequacy at the Coroado’s Association of Senior Citizens, Manaus (Amazonas, Brazil) - Silva, Geislayne Mendonça (2020)
The Coroado’s Association of Senior Citizens (Portuguese acronym: ASSIC) in partnership with the Coroado’s Program/UFAM, Manaus (Amazonas, Brazil), have developed studies to adapt their facilities, among them the research for designing furniture solutions through the reuse of pallets and Social Design guidelines, presented in this article. These solutions proved to be easily manufactured and an alternative of income generation for local carpenters due to the low cost of execution, the value added to the final products and the acceptance of users.